The Mediating Role Of Strategic Leadership Advantage In Improving Organizational Performance At The Indonesia Army Hospital - Mohan, Verawaty; Arafah, Willy; Anggiani, Sarfilianty (Journal of Comprehensive Science, 2025)
The leadership strategy at the Indonesian Army Hospital that has driven increased efficiency and quality of service, employees must also have the ability to innovate. In an increasingly complex and dynamic environment, innovation is key to maintaining and improving the quality of health services. This research aims to analyze the influence of strategic flexibility, competitive advantage, and employee innovation on organizational performance in the context of TNI Army Hospitals, mediated by strategic leadership. This research is a quantitative research method, with primary data sources, namely using questionnaires distributed directly to respondents. The sampling technique used in this study is saturated sampling (census) with individual units of analysis, specifically targeting 155 top and middle managers at the TNI Hospital. Data collection was cross-sectional using questionnaires distributed online. The data analysis method used is the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the help of SmartPLS version 3.2.9 software. Based on the hypothesis testing results, it was found that strategic flexibility and competitive advantage have a direct effect on organizational performance, while employee innovation does not have a direct effect on organizational performance. Other results indicate that strategic flexibility and competitive advantage have an indirect effect on organizational performance through the mediation variable of strategic leadership. The variable of strategic leadership in this study acts as a partial mediator, because the value of the indirect influence is smaller than the value of the direct influence. Therefore, strategic leadership can strengthen the influence of strategic flexibility and competitive advantage on organizational performance. But it cannot strengthen the influence of employee innovation on organizational performance.